SELF-CONCEPT AND FAMILY ENVIRONMENT AMONG ADOLESCENT STUDENTS IN RELATION TO GENDER AND LOCALE (International Journal of Food and Nutritional Sciences, 2022)
The present study investigates the study of self-concept and family environment of adolescent students. The sample consisted 200 students of class 9th were selected from four different schools of Amritsar (Punjab). In order to test, the hypothesis formulated for the present study. The scores obtained from different tests were subjected to statistical analysis and interpretation. Raw scores were tabulated and analyzed mean scores, standard deviation, standard error and correlation were used to arrive at the conclusions – (i) There exists significant gender difference in the selfconcept of adolescent students. (ii) There is no significant difference between male and female secondary school students in family environment. (iii) There is significant difference in selfconcept of urban and rural secondary school students. (iv)There is significant difference between urban and rural secondary school students in family environment. (V) There is significant relationship between self-concept and family environment.